Haloperidol Induced Sudden Cardiac Arrest—Report of a Very Rare Case and Review of Literature - Parvez Mohi-Ud-Din Dar; Supreet Kaur; Jogendra Boddeda; Sajid Mohammad Wani (Case Reports in Psychiatry)
Haloperidol is a typical antipsychotic drug. This drug is still widely used in emergency medicine, psychiatry, and general medicine departments. It is mostly used for acute confusional state, psychotic disorders, agitation, delirium, and aggressive behaviour. Overdose of haloperidol can cause sudden deaths. Cardiopulmonary arrest related to use of haloperidol had been reported in literature as case reports but are very few. No such cases have been reported in India till now. We report a case of cardiac arrest due to the use of haloperidol.